Supercritical fluid extraction and purification of astaxanthin from Malaysia tiger shrimp (Penaeus monodon Fabricius) waste - Radzali, Shazana Azfar (2015)
Astaxanthin is claimed to have higher antioxidant activity than that of other carotenoids such as lutein, zeaxanthin, canthaxanthin and β-carotene; the antioxidant activity of astaxanthin is also claimed to be higher than that of α-tocopherol. Penaeus monodon (tiger shrimp) is the largest commercially available shrimp species and its waste is a rich source of carotenoids such as astaxanthin and its esters. The extraction of thermolabile compound like carotenoids at lower temperatures through SFE can reduce the potential isomerization and degradation of the extraction product. The main objectives of this study were to find the optimum conditions for astaxanthin extraction from Tiger shrimp waste as well as to characterize and separate the free astaxanthin and its ester from the pigment extract. The efficient and environmental friendly recovery of astaxanthin was accomplished by using supercritical fluid extraction (SFE) technique. The techniques of identification and quantification of the carotenoids employed in this study were UV spectrophotometric test and high performance liquid chromatography (HPLC) analysis. The effects of different co-solvents and their concentrations on the yield and composition of the extract were investigated in this study. The following co-solvents were studied prior to the optimization of the SFE technique: ethanol, water, methanol, 50% (v/v) ethanol-water, 50% (v/v) methanol-water, 70% (v/v) ethanol-water, and 70% (v/v) methanol-water. The ethanol extract produced the highest carotenoid yield (84.02 ± 0.8μg/g) dry weight (DW) with 97.1% recovery. The ethanol extract also produced the highest amount of the extracted astaxanthin complex (58.03 ± 0.1 μg/g DW) and the free astaxanthin content (12.25 ± 0.9 μg/g DW) in the extract. Lutein and β-carotene were the other carotenoids identified. For optimization study, a central composite design (CCD) was employed to determine the effect of three supercritical carbon dioxide (SC-CO2) parameters namely temperature (X1) from 40 to 80ºC, pressure (X2) from 150 to 250 bar and extraction flow rate (X3) from 1 to 3 ml/min on the astaxanthin yield (Y1) and free astaxanthin content (Y2). The nonlinear regression equations were significantly (p<0.05) fitted for both responses with high R2 (>0.9261), which had no indication of lack of fit. The results indicated that a combined set of values of temperature (56.88ºC), pressure (215.68 bar) and extraction flow rate (1.89 ml/min) was predicted to provide the optimum region in terms of astaxanthin yield, (58.50 ± 2.62 μg/g) and free astaxanthin content (12.20 ± 4.16 μg/g). Later, the free astaxanthin and the isomers of astaxanthin from the extracts of the shrimp waste were successfully separated using open column chromatography (OCC). Three kinds of astaxanthin isomers; trans-astaxanthin (478.8 nm), 9-cis-astaxanthin (470.4 nm), 13-cis-astaxanthin (468.0 nm) and their esters were separated and identified according to their retention behaviour, absorbance spectra and absorption maxima by photodiode array detection. The purified astaxanthin contained approximately 85.896% (3S, 3’S)-trans astaxanthin (free astaxanthin), 1.944% 9-cis-astaxanthin, 3.681% 13-cis-astaxanthin, 2.825% lutein and 4.421% impurities. These findings highlighted the potential of SFE of astaxanthin and the chromatographic analysis suitable for the recovery of astaxanthin from shrimp waste. This can reduce the problems related to waste disposal itself and solvent extraction which may post a dangerous threat to the environment.